Green and highly durable repair material suitable for humid environments and preparation method thereof
By modifying high-magnesium nickel slag in weak acid wet-grinding environment, the problems of insufficient water resistance and high cost in humid environments are solved, and early strength improvement and durability extension are achieved, forming a green and environmentally friendly high durability Repairing materials.
Patent Information
- Application Number
- CN202310195100.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-03
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2043-03-03
AI Technical Summary
Magnesium phosphate cement has insufficient water resistance in humid environments, high cost, short hydration time, low early strength, and slow strength due to nickel slag replacing magnesium oxide, which affects its application.
Modify high-magnesium nickel slag in a weakly acidic wet grinding environment, and form a porous cationic film by fully decomposing its internal minerals, improving the Mg2+ dissociation efficiency, combining the retarding effect of citric acid and boric acid solutions, delaying the hydration process, and forming a Magnesium phosphate cement with high bond strength.
It achieves the use of industrial solid waste while ensuring the strength stability of magnesium phosphate cement, while reducing costs, extending retarding time, improving water resistance and durability, and improving industrial solid waste utilization, forming a green and environmentally friendly high-durability repair material.
Smart Images

Figure BDA0004106854210000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a green and highly durable repair material suitable for a humid environment and a preparation method thereof. Background Art
[0002] With the rapid economic development of our country, the number of buildings such as houses and bridges has increased sharply. However, as time goes by, these buildings are suffering from damage due to inadequate design details and construction as well as damage caused by natural disasters. In order to prevent further deterioration of the buildings, some repair materials are used. Magnesium phosphate cement is a magnesium phosphate cementitious material generated by acid-base reaction of dead-burned MgO and potassium dihydrogen phosphate. It has the characteristics of fast setting and hardening, high early strength, and good biocompatibility. It is widely used in the field of repair materials, but magnesium phosphate cement still has many shortcomings. For example, one of its raw materials, dead-burned magnesium oxide, refers to the product obtained by forging magnesite at a high temperature of 1500-1700℃. A large amount of CO is released during the forging process of dead-burned magnesium oxide. 2 It will cause serious pollution to the environment. To produce 1 ton of dead-burned magnesium oxide, 0.11-0.5 ton of coal is consumed, and 10-25 kw·h of electricity is consumed. The price range is 12000-18000 r / t, and the cost is relatively high.
[0003] Water resistance and corrosion resistance are also the most critical parts of the performance of repair materials. Due to the low solubility of phosphate in the MKPC system, water will slowly penetrate into the MKPC structure in a humid environment and dissolve the phosphate, reducing the phosphate component in the structure in the later stage of hydration. The hydration reaction cannot be fully carried out, and the generated hydration products are insufficient, which leads to increased structural porosity and low water resistance.
[0004] Nickel slag is a granular solid waste formed by quenching high-temperature melt during the smelting of nickel metal or nickel-iron alloy. Due to the lack of efficient and mature treatment technology, the cumulative output of nickel slag has reached tens of millions of tons. The large amount of stored nickel slag not only occupies public resources but also has an adverse impact on the surrounding environment. The internal properties of nickel slag have changed after different processing techniques. One of the products, high-magnesium nickel slag, has high magnesium and silicon content. The mineral phase mainly exists in the form of glassy matter and has the potential volcanic ash activity. It is used in magnesium phosphate cement to replace dead-burned magnesium oxide. High-magnesium nickel slag also has a good particle grading, which can make magnesium phosphate cement more compact and improve some of its durability. However, the Mg dissolved in high-magnesium nickel slag 2+The relatively low content, low hydration rate, and small amount of K-type struvite produced during the hydration process lead to a decrease in the overall strength of the MKPC structure. In addition, due to other impurities contained in it, it cannot replace heavy-burned magnesium oxide in large amounts. The utilization rate of industrial solid waste is low, and the potential activity inside the nickel slag is not fully stimulated. Therefore, it is crucial to provide a new method to improve the utilization rate of high-magnesium nickel slag while ensuring the strength stability of magnesium phosphate cement.
[0005] Prior art CN112573848A discloses a modification of magnesium phosphate cement and its preparation method, which adds a portion of light magnesium oxide and a large amount of phosphogypsum to the original material, slows down the hydration and coagulation rate to a certain extent, and has the characteristics of high strength and stability. However, the early strength is insufficient and the water resistance is poor.
[0006] Prior art CN106495646A discloses a modification of magnesium phosphate cement and a preparation method thereof, which adds a certain amount of coral powder and nickel slag powder to the original magnesium phosphate cement and mixes with seawater, so that the material has the characteristics of controllable setting time and good water resistance. However, the overall strength is low due to the corrosive effect of seawater.
[0007] Green development is the mainstream development in the current construction industry. It is of great significance to carry out green economic improvements on the basis of ensuring the strength of magnesium phosphate cement. Summary of the invention
[0008] In view of the current shortcomings of magnesium phosphate cement, such as high cost, short hydration time, and insufficient water resistance, and the fact that nickel slag replaces magnesium oxide, resulting in low early strength and slow strength development, the present invention provides a green, environmentally friendly, high early strength, good water resistance and high durability magnesium phosphate cement and its preparation method. At the same time, the weakly acidic wet grinding environment can efficiently decompose the glass in the nickel slag, improve the Mg 2+ The dissociation efficiency makes the material have the characteristics of high bonding strength, small shrinkage, high durability, good working performance and high utilization rate of industrial solid waste.
[0009] To achieve the above object, the technical solution of the present invention is as follows:
[0010] In a first aspect, the present invention provides a green and highly durable repair material suitable for humid environments, characterized in that it comprises the following components, measured by mass: 400-450 parts of high-magnesium nickel slag, 300-400 parts of dead-burned magnesium oxide, 200-250 parts of potassium dihydrogen phosphate, 200-225 parts of weak acid solution, 10-15 parts of retarder, 100-150 parts of water, 8-12 parts of water reducer, and 1000 parts of quartz sand.
[0011] In a second aspect, the present invention provides a method for preparing the green and highly durable repair material suitable for a humid environment as described above, characterized in that it comprises the following steps:
[0012] S1) feeding 400-450 parts of high-magnesium-nickel slag into a drum ball mill and grinding for 1.5-2h, then sieving to remove the residue to obtain high-magnesium-nickel slag powder, wherein the obtained high-magnesium-nickel slag powder has a particle size of 10-18 μm;
[0013] S2) mixing 400-450 parts of the high-magnesium-nickel slag powder obtained in step S1) and 200-225 parts of the weak acid solution, stirring them evenly, and then placing them in a wet ball mill for wet grinding for 40-60 minutes to obtain a high-magnesium-nickel slag slurry;
[0014] S3) The slurry obtained in step S2) is mixed with 300-400 parts of dead-burned magnesium oxide, 200-250 parts of potassium dihydrogen phosphate, and 10-15 parts of retarder, and then placed in a mortar mixer and slowly stirred at 60r / min for 30s, then 8-12 parts of water reducer and 100-150 parts of water are placed in the mortar mixer and slowly stirred for 30s, then 1000 parts of quartz sand are placed in the mortar mixer and slowly stirred for 30s, and then quickly stirred at 120r / min for 30s to obtain a green and highly durable repair material.
[0015] As a preferred solution, the specific surface area of the high magnesium-nickel slag taken in step S1) is 460-550m 2 / kg, the MgO content is ≥30%; the speed of the drum ball mill is 400-500r / min.
[0016] Furthermore, the weak acid solution in step S2) is a citric acid solution or a saturated boric acid solution with a concentration of 0.026-0.03 g / L;
[0017] The particle size of the high-magnesium-nickel slag slurry obtained in step S2) is 1-3 μm, and the rotation speed of the wet ball mill is 600-700 r / min.
[0018] Furthermore, in step S3), the calcination temperature of the dead-burned magnesium oxide is 1600-1700°C, and the specific surface area is 275-285m 2 / kg, density is 3.41-3.58g / cm 3 Minimum particle size ≥30μm;
[0019] The purity of potassium dihydrogen phosphate in step S3) is ≥ 99%;
[0020] In the step S3), the retarder is borax pentahydrate with a purity of ≥99%.
[0021] The water reducing agent in step S3) is a polycarboxylate water reducing agent with a molecular weight of 1100-1200 g / mol, a solid content of 40-45%, and a water reduction rate of ≥25%;
[0022] In the step S3), the quartz sand includes quartz sand A with a particle size range of 0.5 mm-2 mm and quartz sand B with a particle size range of 0-0.5 mm, and the mass ratio of quartz sand A to quartz sand B is 1:1.
[0023] Compared with the prior art, the present invention selects wet grinding in a weak acid environment and has the following advantages and beneficial effects:
[0024] The present invention modifies high-magnesium nickel slag in an acidic wet grinding environment to replace magnesium oxide, effectively reducing costs while ensuring the basic properties of magnesium phosphate cement, making full use of solid waste, delaying slow setting time, and increasing its water resistance and corrosion resistance. The specific advantages are:
[0025] 1. In the weak acid wet grinding environment, the internal minerals of high magnesium nickel slag are fully decomposed, the Mg-O bond is broken, and the anion and cation transfer between the particle surface and the solution forms a potential difference, which promotes the dissolution of ions and forms a porous cationic film on the particle surface, avoiding the condensation phenomenon between the particles and making the destruction more uniform and thorough. Compared with ordinary wet grinding, the acidic environment has the effect of aiding grinding, which can further refine the high magnesium nickel slag particles and form the nucleation seeds of the particles. It plays an inductive role, and gives full play to its filling effect and micro-aggregate effect in the subsequent cement hardening process to make the structure more compact; at the same time, it fully decomposes the MgSiO3 contained in the high magnesium nickel slag and produces a large amount of Mg 2+ , reducing the impact of other impurities on the hydration process and improving the hydration efficiency. 2+ , the utilization rate of industrial solid waste is high, it is environmentally friendly, and achieves the advantages of economy and green.
[0026] 2. Considering that the increase in the pH value in the solution may cause more extensive deprotonation of the groups, the weak acid wet grinding environment also provides sufficient H + , to prevent excessive OH - Consumption of Mg 2+ Mg(OH)2 is generated, and under acidic conditions, part of the forsterite in the high-Mg-Ni slag reacts with H + The reaction generates nano-silicon dioxide, which further fills the pores and enhances the mechanical strength and durability of the material. In addition, with the large amount of high-magnesium-nickel slag powder, as the pH value of the MKPC hardened body changes from weak acid to weak alkaline, the glassy body of the high-magnesium-nickel slag powder releases Si 2+ 、Al 3+ The volcanic ash reaction with hydroxide stimulates the potential activity of the high-magnesium-nickel slag, gradually generating hydration products to further fill the pores.
[0027] 3. In the weak acid wet grinding environment, citric acid and dissolved Mg 2+ It will undergo unstable chelation, and the resulting complex will form a protective film and wrap the particles. The boric acid solution itself is also a retarder, and both play a certain retarding role. And the acidity of the solution is controlled to be greater than that of potassium dihydrogen phosphate, thereby inhibiting the decomposition of potassium dihydrogen phosphate, delaying the hydration process, and achieving a further retarding effect.
[0028] It is particularly noted that the present invention uses industrial waste, wet-grinds in an acidic environment, fully stimulates the potential activity of industrial waste, and uses it to replace the raw material dead-burned magnesium oxide, while reducing costs to ensure that its mechanical properties will not be reduced, and strengthens the various properties of the present invention through better particle grading (weak acid plays a grinding aid effect), volcanic ash effect, inhibition of acid-base neutralization reaction, chelation of citric acid and other different aspects, and its high yield can be guaranteed. Compared with the prior art, the present invention is not just a simple increase on the basis of raw materials, but a method to improve the replacement of raw materials by a substance, ensuring that there is no loss in performance, and optimizing the retarding time and water resistance. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is further clearly and completely explained below in conjunction with specific embodiments.
[0030] In the following embodiments, the nickel slag used is industrial solid waste nickel slag produced by industrial manufacturing of nickel alloy, and its MgO content exceeds 30%; the calcination temperature of the dead-burned magnesium oxide used is 1700°C, the purity of the potassium dihydrogen phosphate used is ≥99%, and the retarder used is borax pentahydrate, and its purity is ≥99%. The specific surface areas of the nickel slag and the dead-burned magnesium oxide are 460-550m 2 / kg, 275-285m 2 / kg The selected weak acid solution is a citric acid solution with a concentration of 0.03g / L or a saturated boric acid solution, and the parts of each raw material are parts by mass.
[0031] Embodiment 1:
[0032] 1) 400 parts of high-magnesium-nickel slag were fed into a drum ball mill and ground for 2 hours, then sieved to remove the slag and sieved to obtain high-magnesium-nickel slag powder with a median particle size of 7.5 μm;
[0033] 2) 400 parts of the high-magnesium-nickel slag powder obtained in step 1) and 210 parts of a 0.026% citric acid solution were mixed and stirred evenly, and then placed in a vertical ball mill for wet grinding for 40 minutes to obtain a high-magnesium-nickel slag slurry with a median particle size of 5.2 μm;
[0034] 3) The slurry obtained in step 2) is slowly stirred for 30 seconds with 350 parts of dead-burned magnesium oxide, 250 parts of potassium dihydrogen phosphate, and 15 parts of retarder, and then 9 parts of polycarboxylate water reducer and 150 parts of water are placed in a mortar mixer and slowly stirred for 30 seconds, and then 1000 parts of quartz sand are placed in a mortar mixer and slowly stirred for 30 seconds, and then quickly stirred for 30 seconds to form a magnesium phosphate cement repair material.
[0035] Embodiment 2:
[0036] 1) 420 parts of high-magnesium-nickel slag were fed into a drum ball mill and ground for 2 hours, then sieved to remove the slag and sieved to obtain high-magnesium-nickel slag powder with a median particle size of 7.6 μm;
[0037] 2) 420 parts of the high-magnesium-nickel slag powder obtained in step 1) and 220 parts of a 0.03% citric acid solution were mixed and stirred evenly, and then placed in a vertical ball mill for wet grinding for 60 minutes to obtain a high-magnesium-nickel slag slurry with a median particle size of 4.8 μm;
[0038] 3) The slurry obtained in step 2) is slowly stirred for 30 seconds with 350 parts of dead-burned magnesium oxide, 230 parts of potassium dihydrogen phosphate, and 14 parts of retarder, and then 9 parts of polycarboxylate water reducer and 130 parts of water are placed in a mortar mixer and slowly stirred for 30 seconds, and then 1000 parts of quartz sand are placed in a mortar mixer and slowly stirred for 30 seconds, and then quickly stirred for 30 seconds to form a magnesium phosphate cement repair material.
[0039] Embodiment 3:
[0040] 1) 440 parts of high-magnesium-nickel slag were fed into a drum ball mill and ground for 2 hours, then sieved to remove the slag and sieved to obtain high-magnesium-nickel slag powder with a median particle size of 7.7 μm;
[0041] 2) 440 parts of high-magnesium-nickel slag powder obtained in step 1) and 230 parts of saturated boric acid solution were mixed and stirred evenly, and then placed in a vertical ball mill for wet grinding for 40 minutes to obtain a high-magnesium-nickel slag slurry with a median particle size of 5.4 μm;
[0042] 3) The slurry obtained in step 2) is slowly stirred for 30 seconds with 350 parts of dead-burned magnesium oxide, 210 parts of potassium dihydrogen phosphate, and 13 parts of retarder, and then 9 parts of polycarboxylate water reducer and 110 parts of water are placed in a mortar mixer and slowly stirred for 30 seconds, and then 1000 parts of quartz sand are placed in a mortar mixer and slowly stirred for 30 seconds, and then quickly stirred for 30 seconds to form a magnesium phosphate cement repair material.
[0043] Embodiment 4:
[0044] 1) 450 parts of high-magnesium-nickel slag were fed into a drum ball mill and ground for 2 hours, then sieved to remove the slag and sieved to obtain high-magnesium-nickel slag powder with a median particle size of 7.8 μm;
[0045] 2) 450 parts of the high-magnesium-nickel slag powder obtained in step 1) and 250 parts of a saturated boric acid solution were mixed and stirred uniformly, and then placed in a vertical ball mill for wet grinding for 60 minutes to obtain a high-magnesium-nickel slag slurry with a median particle size of 4.9 μm;
[0046] 3) The slurry obtained in step 2) is slowly stirred for 30 seconds with 350 parts of dead-burned magnesium oxide, 200 parts of potassium dihydrogen phosphate, and 11 parts of retarder, and then 9 parts of polycarboxylate water reducer and 100 parts of water are placed in a mortar mixer and slowly stirred for 30 seconds, and then 1000 parts of quartz sand are placed in a mortar mixer and slowly stirred for 30 seconds, and then quickly stirred for 30 seconds to form a magnesium phosphate cement repair material.
[0047] Comparative Example 1:
[0048] 1) 750 parts of dead-burned magnesium oxide, 250 parts of potassium dihydrogen phosphate, and 12 parts of retarder are slowly stirred for 30 seconds, and then 12 parts of polycarboxylate water reducer and 350 parts of water are placed in a mortar mixer and slowly stirred for 30 seconds, and then 1000 parts of quartz sand are placed in the mortar mixer and slowly stirred for 30 seconds, and then quickly stirred for 30 seconds to form magnesium phosphate cement.
[0049] Comparative Example 2:
[0050] 1) 800 parts of dead-burned magnesium oxide, 200 parts of potassium dihydrogen phosphate, and 15 parts of retarder are slowly stirred for 30 seconds, and then 12 parts of polycarboxylate water reducer and 350 parts of water are placed in a mortar mixer and slowly stirred for 30 seconds, and then 1000 parts of quartz sand are placed in the mortar mixer and slowly stirred for 30 seconds, and then quickly stirred for 30 seconds to form magnesium phosphate cement.
[0051] The raw materials used in the above examples and comparative examples for preparing the various gelling materials are the same, and the performance indicators are shown in Table 1.
[0052] The tested data are as follows: the fluidity test is carried out according to the requirements of the national standard "Test Method for Fluidity of Cement Mortar" (GB / T2419-2005), the cement compressive strength test is carried out according to the requirements of the national standard "Test Method for Strength of Cement Mortar" (GB / T17671-1999), the loading speed is set to 2.4 kN / s, the number of test blocks is 3, the setting time is carried out according to the requirements of "Water Consistency, Setting Time and Stability of Cement Standard Consistency" (GB / T1346-2011), the water resistance of cement is reflected by measuring its volume change rate, and it is carried out according to the requirements of "Test Method for Shrinkage of Cement Mortar" (JC / T603-2004), and the curing conditions of the test blocks in the above embodiments are all water curing.
[0053] Table 1:
[0054]
[0055] It can be seen from the above table that the magnesium phosphate cement prepared by the present invention is used as a repair material, and its early strength is large, and the retarding time is extended to a certain extent, the 28d strength is significantly improved, the later volume change rate is small, the structural porosity is reduced to make the structure more compact, and the durability and water resistance of the repair material are guaranteed.
[0056] In summary, the present invention adopts a method to improve the shortcomings of magnesium phosphate cement, such as short retarding time and insufficient water resistance. From the comparative examples and embodiments, the present invention has been enhanced in terms of early strength, overall strength and water resistance, which shows that the potential activity of nickel slag is fully utilized. The extension of the retarding time shows that the weak acid wet grinding environment can hinder the acid-base neutralization reaction in magnesium phosphate cement.
[0057] The above embodiments are only illustrative of the principles and effects of the present invention, and cannot be used to limit the scope of the present invention. Those skilled in the art can modify or change the above embodiments without violating the spirit and scope of the present invention. Therefore, the test groups described are only part of the test groups of the present invention, rather than all the test groups. Based on the test groups in the present invention, all other test groups obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
Claims
1. A green and highly durable repair material suitable for humid environments, characterized by: The following components are included by mass: 400-450 parts of high-magnesium nickel slag, 300-400 parts of dead-burned magnesium oxide, 200-250 parts of potassium dihydrogen phosphate, 200-225 parts of weak acid solution, 10-15 parts of retarder, 100-150 parts of water, 8-12 parts of water reducer, and 1000 parts of quartz sand; The green and highly durable repair material suitable for humid environments is prepared by the following method, which specifically comprises the following steps: S1) 400-450 parts of high-magnesium-nickel slag are fed into a drum ball mill and ground for 1.5-2 hours, and then sieved to remove the residue to obtain high-magnesium-nickel slag powder, wherein the obtained high-magnesium-nickel slag powder has a particle size of 10-18 μm; the specific surface area of the high-magnesium-nickel slag obtained in step S1) is 460-550 m 2 / kg, MgO content ≥30%; the speed of the drum ball mill is 400-500r / min; S2) 400-450 parts of the high-magnesium-nickel slag powder obtained in step S1) and 200-225 parts of the weak acid solution are mixed and stirred evenly, and then placed in a wet ball mill for wet grinding for 40-60 minutes to obtain a high-magnesium-nickel slag slurry; the weak acid solution in step S2) is a citric acid solution or a saturated boric acid solution with a concentration of 0.026-0.03g / L; the obtained high-magnesium-nickel slag slurry has a particle size of 1-3μm, and the speed of the wet ball mill is 600-700r / min; S3) the slurry obtained in step S2) is mixed with 300-400 parts of dead-burned magnesium oxide, 200-250 parts of potassium dihydrogen phosphate, and 10-15 parts of retarder, and then placed in a mortar mixer and slowly stirred at a speed of 60r / min for 30s, then 8-12 parts of water reducer and 100-150 parts of water are placed in the mortar mixer and slowly stirred for 30s, then 1000 parts of quartz sand are placed in the mortar mixer and slowly stirred for 30s, and then quickly stirred at a speed of 120r / min for 30s to obtain a green and highly durable repair material; In step S3), the calcination temperature of the dead-burned magnesium oxide is 1600-1700°C, and the specific surface area is 275-285m 2 / kg, density is 3.41-3.58g / cm 3 The minimum particle size is ≥30μm; the purity of potassium dihydrogen phosphate is ≥99%; the retarder is borax pentahydrate with a purity of ≥99%; the water reducer is a polycarboxylic acid water reducer with a molecular weight of 1100-1200g / mol, a solid content of 40-45%, and a water reduction rate of ≥25%; the quartz sand includes quartz sand A with a particle size range of 0.5mm-2mm and quartz sand B with a particle size range of 0-0.5mm, and the mass ratio of quartz sand A to quartz sand B is 1:1.
